Landslide Susceptibility Mapping With Aerial Photographs And Weight Of Evidence Model - Goutham Priya M., Jeyaarthi A. J., Hemavathy M. (International Journal of Advanced Science and Technology, 2020)
A landslide, solitary of the catastrophes, is a most important crisis besides damaging livelihood of hundreds of people their properties and communication. During monsoon season, the instability of geology and geomorphology causes the predicament of landslides further exasperated. In broad-spectrum, the parameters which manipulate the occurrence of a landslide include gradient, weather, moisture, land cover land use. In this study a “working methodology” has been employed in which the parameters like slope, soil, geology, proximity to road, river and earlier landslide locations are statistically investigated with a model to prepare landslide susceptible areas using photogrammetric products and geographic information system (GIS). Weights of evidence model is worn to forecast a theory about an incident based on providing the known evidence of the incidents in the study area where adequate data are accessible to compute approximately the virtual significance of each substantiation through statistical methods. Positive and negative weights and contrast values have been calculated for various classes of parameters used in the study. Amid the different categories of land use/land cover, scour region have highest probability and is further susceptible to landslides because of slope stability due to deforestation of dense forest area. In the study area, it was concluded that the noteworthy contributors are the gradient of class of 35–50°. The susceptibility map shows that around 41.5% of the study area has very high susceptibility, 30% high susceptibility, 11.2% in moderate and 17. 2% in the low susceptibility category. It has been seen that only a moderate variation is there between the model and expert opinion method. It is good to apply this method to smaller areas but when more area is taken under the study Expert’s opinion method is not appropriate